Optimizing the addition of Skeletonema Costatum flour in feed for the growth and survival of koi fish (Cyprinus carpio) - Hakim, Riza Rahman; Hidayat, Reyhan Rafisyah; Hermawan, David; Prasetyo, Dony (Universitas Malikussaleh, 2025)
Selecting the appropriate feed is one of the most important factors in cultivating koi fish. High-quality feed is feed that contains a comprehensive range of essential nutrients, including protein, fat, carbs, vitamins, and minerals. Skeletonema costatum, which has a protein content of approximately 31%, is a good dietary option for promoting the growth of koi fish. This research aims to determine the effect of providing skeletonema flour on the growth and survival of Koi fish. The method used is experimental. The research design used a completely randomized design (CRD) with five treatments and three replications. The treatment used in this research was the addition of skeletonema flour to the feed at different doses, namely P0 (0%), P1 (1%), P2 (3%), P3 (5%), and P4 (7%). The results of the research showed that the addition of Skeletonema costatum flour to artificial feed gave effective results in increasing absolute weight growth but had no effect on absolute length growth, FCR, or survival of koi fish. The best treatment was treatment P4, namely the addition of 7% skeletonema flour, which resulted in an absolute weight growth of 2.3 grams and the lowest FCR.Keywords: Growth; Koi Fish; Skeletonema costatum; Survival Rate